DEVELOPMENT OF ZAKAT INFORMATION SYSTEM FOR THE ABC ZAKAT INFAQ SHADAQAH CHARITY BASED ON WEBSITE - Adi Imantoyo; Arnolis; Helvin. S (Department of Information System Muhammadiyah University of Riau, 2024)
Information System is a collection of interconnected elements that work together to gather, process, store, and disseminate information that is beneficial to users. The method used in implementing this project is the sequential linear method, which has several stages, including analysis, design, coding, and testing. . The result of this research Zakat information system based on a website for the ABC Zakat, Infaq, and Shadaqah Amil Zakat Institution using the Laravel framework that utilizes the PHP programming language and is connected to the MySQL database. This system is valuable in enhancing the efficiency, transparency of Zakat management, and distributing funds more effectively within the ABC Zakat, Infaq, and Shadaqah Amil Zakat Institution (LAZIS) ABC.